Ameliorative Effect of Faidherbia albida Against 2.4-Dinitrophenylhydrazine Induced Hyperbilirubinemia in Wistar Albino Rats - Tukur MI; Abubakar IB; Fakai IM; Danjuma JB; Malami I; Muhammad A (Dove Medical Press, 2024)
Maryam Ibrahim Tukur,1 Ibrahim Babangida Abubakar,2 Isah Musa Fakai,1 Jamilu Bala Danjuma,1 Ibrahim Malami,3 Aliyu Muhammad4 1Department of Biochemistry, Faculty of Life Sciences, Kebbi State University of Science and Technology, Aliero, Kebbi State, Nigeria; 2Department of Biochemistry, Faculty of Biomedical Sciences, Kampala International University, Kampala, Uganda; 3Department of Pharmacognosy and Ethnopharmacy, Faculty of Pharmaceutical Sciences, Usmanu Danfodio University, Sokoto, Nigeria; 4Department of Biochemistry, Faculty of Life Sciences, Ahmadu Bello University Zaria, Zaria, 810271, NigeriaCorrespondence: Ibrahim Babangida Abubakar, Email Ibrahim.iba@kiu.ac.ugBackground: Faidherbia albida, popularly known as gawo in Hausa, is traditionally used to treat jaundice in Zuru emirate of Kebbi State. Herein, the ameliorative effect of F. albida against 2.4-dinitrophenylhydrazine-induced hyperbilirubinemia in Wistar albino rats was investigated.Methods: Thirty healthy rats were administered 75 mg of 2.4-dinitrophenylhydrazine to induce hyperbilirubinemia. Thereafter, groups 1- 3 received 500, 750, and 1000 mg/kg body weight of the methanol stem-bark extract, and 15 mg/kg of phenobarbitone (standard drug) was administered to group 4. Groups 5 and 6 served as the untreated and normal controls, respectively. The phytochemical composition was evaluated using standard methods, and acute oral toxicity was evaluated using standard OECD 2008 guidelines.Results: Phytochemical analysis revealed the presence of alkaloids, phenols, and a substantial amount of tannins. A significant (P< 0.05) reduction of direct bilirubin, total bilirubin, and total protein levels for all the doses of the extract and standard drug compared to untreated groups was observed. Similarly, there were significant reductions in serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) levels of the group treated with the standard drug and all extract-treated groups compared to elevated levels observed in untreated controls. However, a significant (P< 0.05) increase in serum albumin (ALB) levels, red blood cells, hemoglobin, and pack cell volume was observed in all extract-treated compared to the untreated control in contrast to a significant decrease in MCH levels in treated groups compared to the untreated group.Conclusion: F. albida ameliorated the hyperbilirubinemia induced by 2.4-dinitrophenylhydrazine in Wistar albino rats, thus providing some support for its use in traditional medicine to treat jaundice.Keywords: Faidherbia albida, jaundice, liver enzymes, hyperbilirubinemia, 2, 4-dinitrophenylhydrazine, red blood cells